Konsep Pendidik Menurut Ahmad Tafsir dalam Buku Filsafat Pendidikan Islami dan Relevansinya Terhadap Pendidikan Islam Kontemporer - Nur Inayyah; Muhammad Yunan Harahap; Nurhalima Tambunan (Medan Resource Center, 2026)
This study aims to analyze Ahmad Tafsir’s concept of the educator as articulated in his work Filsafat Pendidikan Islami: Integrasi Jasmani, Rohani, dan Kalbu Memanusiakan Manusia. This study is significant because contemporary Islamic education faces serious challenges, including spiritual degradation, the weakening of character education, and the declining quality and role of educators. This research employs a library research method with a descriptive-analytical approach. Data were analyzed through careful reading, interpretation, and critical examination of Ahmad Tafsir’s ideas concerning the integration of human potential, the role of educators, and the relevance of these concepts in contemporary Islamic education. The findings reveal that Ahmad Tafsir conceptualizes educators as central agents in the process of humanizing individuals through the integrated development of physical, intellectual, spiritual, and inner (qalb) dimensions. Therefore, educators are not merely transmitters of knowledge but also guides who nurture spirituality, cultivate moral character, and exemplify ethical values. This holistic, tauhid-based educational concept remains highly relevant in addressing the challenges of modern education.